Multimodality Therapy for Chronic Pain Syndrome in Critical Lower Extremity Ischemia - I. E. Golub; A. Yu. Novikov; L. V. Sorokina; A. V. Neupokoeva (Общая реаниматология)
Objective: to evaluate the efficiency of multimodal epidural analgesia (EA) in patients with chronic critical lower extremity ischemia (CLEI) in the preoperative period. Subjects and methods. A prospective randomized controlled study was conducted in 150 patients.According to the anesthesia mode, the patients were divided into 5 groups: 1) EA with a local anesthetic; 2) EA in combination with a nonsteroidal anti-inflammatory drug (ketoprophen); 3) EA in combination with ketoprophen and subnarcotic doses of ketamine; 4) EA in combination with fentanyl and ketoprophen; 5) EA in combination with fentanyl, ketoprophen, and ketamine. Results. The developed procedure for prolonged multimodal EA allows the stabilization of hemodynamics, the concentration of cortisol and metabolites (glucose, lactate), and the values of regional blood flow. Conclusion. EA with a local anesthetic in combination with fentanyl, ketoprophen, and ketamine is the most effective method for analgesia in patients with CLEI in the preoperative period. Key words: multimodal analgesia.